2011
DOI: 10.1007/s00586-011-2018-9
|View full text |Cite
|
Sign up to set email alerts
|

Centralization in patients with sciatica: are pain responses to repeated movement and positioning associated with outcome or types of disc lesions?

Abstract: In patients with sciatica, centralization was common and associated with improvement in activity limitation and leg pain. Centralization was very common in ruptured disc therefore the study does not support the theory, that centralization only occurs if the intra-discal hydrostatic mechanism is functional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…Table shows the main characteristics of the 23 included studies. Of the 14 included cohorts, two were population based (Miranda et al., ; Tubach et al., ), one cohort [three articles (Vroomen et al., , , b)] reported on patients from primary care and 11 cohorts [18 articles (Bush et al., ; Atlas et al., , , , ; Valls et al., ; Edwards et al., ; Jensen et al., ; Karppinen et al., ; Peul et al., , b; Rasmussen et al., ; Freedman et al., ; Olson et al., ; Rihn et al., ; Suri et al., ; Albert et al., ; Jacobsen et al., )] on patients from secondary care. The diagnosis of sciatica in five cohorts was confirmed with diagnostic imaging [nine articles (Karppinen et al., ; Peul et al., , b; Atlas et al., ; Freedman et al., ; Olson et al., ; Rihn et al., ; Suri et al., ; Jacobsen et al., )], seven cohorts based the diagnosis primarily on clinical criteria [12 articles (Bush et al., ; Atlas et al., , , ; Vroomen et al., , , b; Valls et al., ; Edwards et al., ; Jensen et al., ; Rasmussen et al., ; Albert et al., )] and two cohorts on self‐reported presence of back pain radiating to the leg (Miranda et al., ; Tubach et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the main characteristics of the 23 included studies. Of the 14 included cohorts, two were population based (Miranda et al., ; Tubach et al., ), one cohort [three articles (Vroomen et al., , , b)] reported on patients from primary care and 11 cohorts [18 articles (Bush et al., ; Atlas et al., , , , ; Valls et al., ; Edwards et al., ; Jensen et al., ; Karppinen et al., ; Peul et al., , b; Rasmussen et al., ; Freedman et al., ; Olson et al., ; Rihn et al., ; Suri et al., ; Albert et al., ; Jacobsen et al., )] on patients from secondary care. The diagnosis of sciatica in five cohorts was confirmed with diagnostic imaging [nine articles (Karppinen et al., ; Peul et al., , b; Atlas et al., ; Freedman et al., ; Olson et al., ; Rihn et al., ; Suri et al., ; Jacobsen et al., )], seven cohorts based the diagnosis primarily on clinical criteria [12 articles (Bush et al., ; Atlas et al., , , ; Vroomen et al., , , b; Valls et al., ; Edwards et al., ; Jensen et al., ; Rasmussen et al., ; Albert et al., )] and two cohorts on self‐reported presence of back pain radiating to the leg (Miranda et al., ; Tubach et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…For a patient with only mid lumbar pain, the pain must cease in order for them to be categorized as a centralizer. However, Albert et al 38 believe that smaller changes in pain location (e.g. distal pain moving proximally from above the ankle to below the knee) must also be recorded as centralization.…”
mentioning
confidence: 99%
“…However, it is unclear how long this upright position must be continued and what normally active is. To categorize the patient as a centralizer, Albert et al 38 suggested that the most distal pain must remain abolished for at least 1 minute after positioning the patient in a weightbearing position. It is difficult to compare our inter-rater reliability findings for the category specific exercises with previously conducted studies that investigate the reliability of MDT.…”
mentioning
confidence: 99%
“…Additionally, this investigation included movement-based physical examination tests commonly used by physical therapists clinically to aid in the assessment and classification of patients with LBP, including symptom peripheralization and/or centralization during lumbar spinal movements in standing. 2,21 These differences in study design and patient population could prove to be clinically meaningful. Patients with sciatica referred to physical therapy may be clinically different from patients referred specifically for EDX testing, particularly if the nature, severity, and/or duration of symptoms influence the medical management of patients with sciatica.…”
Section: T T Conclusionmentioning
confidence: 99%